Multi-view Video Coding for Wireless Channel - Abd Manap, Nurulfajar (2010)
In this paper, a multi-view video system for wireless applications will be presented. The system consists of components for data acquisition, compression, transmission and display. The main feature of the system includes wireless video transmission system for up to four cameras, by which videos can be acquired, encoded and transmitted wirelessly to a receiving station. The video streams can be displayed on a single 3D or on multiple 2D displays. The encoding for the multi-view video through inter-view and temporal redundancies increased the compression rates. The H.264/AVC multi-view compression techniques has been exploited and tested during the implementation process. The video data is then transmitted over a simulated Rayleigh channel through Digital Video Broadcasting – Terrestrial (DVB-T) system with Orthogonal Frequency Division Multiplexing (OFDM). One of the highlights in this paper is the low cost implementation of a multi-view video system, which using only typical web cameras attached to a single PC.